Maternal Eating Practices and Risk Factor of Obesity in Preschool Children - Yunita Indah Prasetyaningrum; Nyoman Kertia; I Made Alit Gunawan (JURNAL NUTRISIA, 2016)
Background: Yogyakarta became one of the cities with quite high prevalence of childhood obesity at 8,98%. In other hand, shifting socio-economic conditions can alter maternal role model of healthy eating practices. These changes related to food intake and incidence of getting obesity in preschool children. Objective: To analyzed maternal eating practices as risk factor of obesity and identified the dominant risk factor related to obesity in preschool children aged 3-5 years. Method: This study was a case control study. Case of this study was obese preschool children (Z-score WHZ > 2 SD) and control of this study was non-obese preschool children (Z-score WHZ -2 ≤ SD ≤ 2). There were 101 obese children and 101 non-obese children based on the nutritional status screening result of 53 early childhood education (ECD) schools in Kota Yogyakarta. Control group was taken by an age and gender matching with the case group. Using Home environment Survey (HES) questionnaire to asses maternal eating practices. The data were analyzed using McNemar test and conditional logistic regression. Results: Maternal eating practices was significantly related to risk of obesity (OR=2,45; p=0,01; 95% CI=1,25-4,84). Maternal eating practices (OR=2,42; p=0,017) and maternal obesity (OR=2,62; p=0,003) were the most dominant risk factors related to the incidence of obesity in preschool children aged 3-5 years. Conclusion: Maternal eating practices and maternal obesity were significantly increase the risk for getting obese in preschool children aged 3-5 years. Key Word: maternal eating practices, maternal obesity, obesity, preschool